The Effectiveness of Attributional Feedback in Improving Perseverance and Learning Achievement of Low-Achievers and Under-Achievers Students in Mathematics of Junior High School Students - Muhammad, Asrori (Advances in Social Sciences Research Journal, 2024)
This experiment tested the hypothesis that students who received oral and written attributional feedback showed higher perseverance and achievement in learning Mathematics than the control group. The subjects of this study were students in grades I and II of Semester II SLTP whose achievement in Mathematics was below the class average. They were categorized as low achievers (SBK) if the scores obtained from the WISC-R Intelligence Test were at or above the average obtained by their peers in this group of research subjects, while the rest were categorized as low achievers (SBR). Students were randomly assigned to one of four treatment groups: (1) oral attributional feedback group; (2) written attributional feedback group; (3) reinforcement feedback group; and (4) no treatment group. The results of ANOVA with LSD test showed that those who received attributional feedback, oral or written, scored significantly higher on the variables of perseverance and achievement in Mathematics compared to the control group students. The comparison group, students who received reinforcement feedback, did not show significant differences in both scores with either the attributional or untreated group. Further factorial design analysis revealed that attributional feedback, both oral and written, was more effective for low achiever students than underachiever students.